Application of a Multidisciplinary Weight of Evidence Approach as a Tool for Monitoring the Ecological Risk of Dredging Activities - d'Errico, Giuseppe; Nardi, Alessandro; Benedetti, Maura; Mezzelani, Marica; Fattorini, Daniele; Di Carlo, Marta; Pittura, Lucia; Giuliani, Maria Elisa; Macchia, Simona; Vitiello, Valentina; Sartori, Davide; Scuderi, Alice; et al. (Frontiers in Marine Science, 2021)
The use of multidisciplinary investigations for the evaluation of aquatic ecosystems status is recommended by the European Directives, but it is still a challenging practice. In this study, we apply a quantitative weight of evidence (WOE) approach (Sediqualsoft) for the integration of extensive data obtained from different typologies of investigations, obtained over a 4-year monitoring study of dredging activities in the harbor of Leghorn (Italy). During different phases of such operations, selected sites have been characterized in terms of levels of trace metals and polycyclic aromatic hydrocarbons in sediments, bioaccumulation of contaminants, and a wide battery of biomarkers in transplanted mussels, ecotoxicological effects of sediments through a battery of bioassays (algal growth inhibition, bioluminescence inhibition, and embryotoxicity tests), and the status of benthic communities. Each typology of data, line of evidence (LOE), has been initially elaborated through dedicated logical flowcharts and algorithms providing specific hazard indices, followed by their overall integration based on different weights assigned to each LOE. This approach allowed to summarize more than 10,000 results, reaching robust conclusions on environmental impact during various phases of dredging operations. This approach was confirmed as a useful tool for monitoring the risk, supporting a “site-oriented” decision making process by providing stakeholders simple interpretation of complex data.